Preparation of FeCo-MOF in-situ modified electrode and electrochemical detection method for paraquat
By modifying the foam nickel electrode in situ by FeCo-MOF, the problems of complex operation of traditional glassy carbon electrodes and easy shedding of active materials are solved, and electrochemical detection with high sensitivity and stability is achieved, suitable for the detection of trace paraquat.
Patent Information
- Application Number
- CN202310180010.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-02-28
AI Technical Summary
In the existing electrochemical detection methods, traditional glass carbon electrodes need to be polished before use, which is complex and time-consuming, and the modification method of active material can easily cause material to fall off and reduce detection performance.
FeCo-MOF is used to modify the foam nickel electrode in situ. By growing FeCo-MOF material in situ on the surface of the foam nickel, the stable load and strong adhesion of the active material are achieved to avoid material falling off.
It improves the sensitivity and stability of electrochemical detection, achieves a high sensitivity response to paraquat, and the detection process is simple, fast and low cost.
Smart Images

Figure CN116106385B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical detection, and in particular to a preparation method of a FeCo-MOF in-situ modified electrode and an electrochemical detection method for paraquat. Background Art
[0002] Paraquat (1,1-dimethyl-4,4-bipyridinium dichloride) is a well-known herbicide widely used in the world. However, paraquat is highly toxic and can remain in the air, soil, water, plants and animals, and its half-life in the environment is as long as 10 years. Paraquat pesticides remaining in the environment can cause serious harm to human health. Acute paraquat poisoning may cause pulmonary fibrosis and be fatal. Trace amounts of paraquat can cause brain damage diseases such as Parkinson's disease. Therefore, the detection of trace amounts of paraquat in the environment and food is of great significance.
[0003] At present, the detection of paraquat usually relies on large and complex equipment, such as high performance liquid chromatography, mass spectrometry, inductively coupled plasma, photochemistry, atomic absorption spectrometry, etc. Although these methods have accurate detection results, they are time-consuming, complex to operate, require professional and skilled personnel, and have high detection costs. Based on the shortcomings of the above-mentioned traditional detection methods, electrochemical sensors have received more and more attention in the detection of paraquat due to their advantages such as simple operation, low cost, high precision, and fast response speed. Among them, the working electrode and active material are the two core parts of the electrochemical sensor. The widely used working electrode is the glassy carbon electrode (GCE). Although its detection performance is stable, the GCE electrode must be polished to the corresponding potential requirements before each use. This operation may take 1-2 days or even longer, and the preliminary processing operation is complicated and time-consuming. It is an important means to select a new electrode with strong conductivity, simple and fast operation to replace the GCE electrode. The performance of the active material of the modified electrode and the way to modify the electrode will also affect the detection performance. The GCE electrode usually uses a drop coating method to modify the interface. This operation may cause the active material to fall off the surface of the GCE electrode, resulting in a change in potential and reducing the detection performance. At the same time, the stronger the conductivity of the active material used to modify the working electrode, the more active sites exposed, which will be conducive to quickly and accurately displaying highly sensitive response electrical signals to different concentrations of paraquat.
[0004] Therefore, in order to improve the electrochemical detection performance and practical application capabilities, it is urgently necessary to select a working electrode that can replace the traditional GCE, to research, design and synthesize active materials with excellent conductivity, rich active sites, and strong electrochemical response, and to improve the method of modifying the working electrode with active materials to construct a highly sensitive electrochemical sensor for trace detection of paraquat molecules. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a preparation method of a FeCo-MOF in-situ modified electrode and an electrochemical detection method for paraquat. The technical solution of the present invention is as follows.
[0006] A method for preparing a FeCo-MOF in-situ modified electrode, comprising:
[0007] Add deionized water and anhydrous ethanol to the N,N-dimethylformamide solution and mix them evenly;
[0008] Add terephthalic acid and dissolve it;
[0009] Add FeCl2·4H2O and CoCl2·6H2O and dissolve them;
[0010] Add hydrofluoric acid and mix well;
[0011] Add the pretreated nickel foam and carry out the reaction at a preset reaction temperature and for a preset reaction time;
[0012] After the reaction is completed, the modified nickel foam is dried at a preset drying temperature for a preset drying time to obtain a FeCo-MOF in-situ modified nickel foam working electrode.
[0013] Preferably, the pretreatment of the nickel foam comprises:
[0014] The nickel foam was sonicated in ethanol;
[0015] After rinsing with deionized water, treating in dilute hydrochloric acid of a preset concentration for a preset cleaning time;
[0016] Rinse with deionized water and dry with cold air.
[0017] Preferably, the modified nickel foam further comprises: washing it alternately with ethanol and deionized water after it is cooled before drying.
[0018] Preferably, the preset concentration of dilute hydrochloric acid is 3M, and the preset cleaning time is 30 minutes.
[0019] Preferably, the preset reaction temperature is 120-150° C., and the preset reaction time is 12-18 hours; the preset drying temperature is 60° C., and the preset drying time is 24 hours.
[0020] A method for electrochemical detection of paraquat, which uses the FeCo-MOF in-situ modified electrode prepared by the above method to electrochemically detect paraquat.
[0021] Preferably, differential pulse voltammetry is used to obtain electrical signals of paraquat at different concentrations, so as to establish a relationship between paraquat concentration and response current.
[0022] Preferably, the sample to be tested is added into a phosphate electrolyte solution having a preset phosphate concentration and a preset pH value.
[0023] Preferably, the preset phosphate concentration is 0.1 M, and the preset pH value is 7.4.
[0024] Preferably, the detection concentration range of paraquat is 1nM~5mM, and the sensitivity of paraquat detection is 123.3μA μM - 1 cm -1 .
[0025] Compared with the prior art, the beneficial technical effect of the present invention is that the present invention selects nickel foam as the working electrode. The highly conductive nickel foam electrode enhances the rapid transmission of the detection current and ensures a highly sensitive response to paraquat. The active material FeCo-MOF has a rich loose porous structure, which can maximize the exposure of rich active sites, achieve a highly sensitive response to paraquat, and has good electrochemical stability, ensuring good reproducibility, selectivity and anti-interference. The active material is modified in the nickel foam by in-situ growth. Compared with the GCE drip coating method, the in-situ growth of FeCo-MOF on the surface of nickel foam can achieve the growth of FeCo-MOF on each surface of nickel foam, the loading amount of active material is increased, the adhesion is strong, and it is not easy to fall off from the electrode surface, and long-term stable detection can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the XRD pattern of FeCo-MOF;
[0027] Figure 2 The SEM images of FeCo-MOF nickel foam electrode at different magnifications;
[0028] FIG3 (a) is a diagram showing the selection of the optimal pH of the electrolyte for detecting paraquat using the FeCo-MOF nickel foam electrode, and FIG3 (b) is a diagram showing the selection of the test scan rate;
[0029] Figure 4 The current difference bar graph of FeCo-MOF nickel foam electrode before and after testing different types of pesticide molecules
[0030] Figure 5 This is a curve diagram of the differential pulse voltammetry test of FeCo-MOF nickel foam electrode before and after the addition of paraquat;
[0031] FIG6 (a) is a differential pulse voltammetry test curve of FeCo-MOF nickel foam electrode for different concentrations of paraquat, and FIG6 (b) is a fitting curve of the corresponding oxidation peak current and concentration;
[0032] FIG. 7 is a curve diagram of paraquat detection in real samples using FeCo-MOF nickel foam electrode. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0034] This example provides a preparation method of a FeCo-MOF in-situ modified electrode and an electrochemical detection method for paraquat, including:
[0035] Preparation of nickel foam working electrode.
[0036] The nickel foam was cut into 1 cm × 2 cm size, placed in ethanol for ultrasonic treatment for 30 minutes to remove organic stains on the surface, washed with deionized water, and then ultrasonically treated in dilute hydrochloric acid for 30 minutes to remove the oxide layer on the surface of the nickel foam skeleton, and then washed with deionized water, and dried with cold air for use. The ethanol was analytically pure, and the dilute hydrochloric acid was analytically pure concentrated hydrochloric acid diluted with deionized water to a concentration of 3 M.
[0037] FeCo-MOF material in situ modified nickel foam electrode.
[0038] Add N, N-dimethylformamide solution to a glass beaker, then add deionized water and anhydrous ethanol respectively, stir evenly under a magnetic stirrer, add terephthalic acid under stirring conditions, continue stirring for 30 minutes, wait until the powder is completely dissolved, continue to add FeCl2·4H2O and CoCl2·6H2O to the solution, stir evenly and dissolve, add a small amount of hydrofluoric acid (HF), stir for 30 minutes, and then transfer the solution to a polytetrafluoroethylene bottle. Put a piece of nickel foam prepared in step 1 into the polytetrafluoroethylene bottle, transfer it to the reactor, react at 120~150℃ for 12~18h, wash it alternately with ethanol and deionized water 3 times after cooling, and dry it at 60℃ for 24h to obtain a FeCo-MOF in-situ modified nickel foam working electrode. Among them, the N, N-dimethylformamide solution, terephthalic acid, FeCl2·4H2O and CoCl2·6H2O are all analytical grade drugs.
[0039] like Figure 1 As shown, by XRD characterization of FeCo-MOF, it can be concluded that the FeCo-MOF material was successfully prepared. Figure 2 The microstructure of FeCo-MOF nickel foam electrode is shown. Figure 2(a) and (b) show that the nickel foam surface is rich in FeCo-MOF, and FeCo-MOF is well anchored on the nickel foam surface and is not easy to fall off from the nickel foam surface; Figure 2 Under the high-magnification microscope in (c), it can be seen that there are many pores, exposing abundant active sites and maximizing the contact area with paraquat.
[0040] Setting up the test conditions for detecting paraquat using FeCo-MOF nickel foam electrode.
[0041] Set the electrolyte pH.
[0042] A certain volume of 0.1M phosphate buffer solution was prepared as the electrolyte solution, and the same volume of electrolyte solution was measured and placed in 6 beakers. Different volumes of 3M hydrochloric acid solution in 1 were added to adjust the pH of the solution to 6, 7, 7.4, 8, 9, 10. Paraquat solution was added to the 6 beakers to ensure that the amount of paraquat contained in each beaker was consistent. The FeCo-MOF nickel foam working electrode, reference electrode and counter electrode were placed in the above solution and tested by differential pulse voltammetry. The pH corresponding to the system with the largest response current was taken as the pH value of the optimal electrolyte solution for the test.
[0043] Specifically, 0.2M potassium dihydrogen phosphate solution and 0.2M potassium dihydrogen phosphate solution were prepared first. A 0.1M potassium phosphate buffer solution was obtained by adjusting the volume of the two solutions. Multiple portions of the same volume of solution were measured, and different volumes of 3M hydrochloric acid solution were added to adjust the pH of the electrolyte to 6, 7, 7.4, 8, 9, 10. 0.1029g of paraquat was dissolved in 40 mL of deionized water to obtain a 0.01M paraquat solution. Different volumes of high-concentration paraquat solution were measured and diluted to 20mL of paraquat solutions with concentrations of 20nM, 20μM and 20mM. The same volume of 20μM paraquat solution was measured and added dropwise to electrolytes of different pH values and stirred evenly. The FeCo-MOF nickel foam electrode, silver / silver chloride reference electrode and platinum counter electrode were placed in the above electrolytes, and the differential pulse voltammetry method was used for testing to obtain the corresponding curves, as shown in Figure 3 (a). As can be seen from Figure 3 (a), when pH = 7.4, the oxidation peak current of the curve is the largest. Therefore, a 0.1 M phosphate solution with a pH of 7.4 was selected as the electrolyte solution for the detection of paraquat.
[0044] Set the scan rate.
[0045] After adding a certain concentration of paraquat solution to the electrolyte solution with the optimal pH, the FeCo-MOF nickel foam working electrode, reference electrode and counter electrode were placed in it, and the cyclic voltammetry method was used to test it. The scan rate was changed for multiple tests, where the scan rate = 20, 40, 50, 60, 80, 100, 120, 140, 160, 180, 200, 220mV / s. According to the response curve, the curve and current are both moderate as the optimal scan rate.
[0046] Specifically, a certain volume of 20 μM paraquat solution was added to the electrolyte solution, stirred evenly, and the FeCo-MOF nickel foam electrode, silver / silver chloride reference electrode and platinum counter electrode were placed therein. Cyclic voltammetry was used for testing, and the scan rate was changed for multiple tests to obtain the corresponding CV curve, as shown in Figure 3 (b). It can be seen from the figure that the response current is small when the scan rate is too low, and the response curve is easily distorted when the scan rate is too high. Therefore, 100 mV / s was selected as the optimal scan rate parameter.
[0047] FeCo-MOF nickel foam electrode was used to sense and detect the selectivity and electrochemical response of paraquat.
[0048] Prepare 20mL of 10μM solutions of dinotefuran, thiamethoxam, imidacloprid, phoxim and carbendazim as comparative solutions for selectivity testing. Measure 200mL of 0.1M, pH=7.4 electrolyte solution in an electrolytic cell, and place FeCo-MOF-modified nickel foam electrode as working electrode, silver / silver chloride electrode as reference electrode and platinum sheet counter electrode in the electrolytic cell. Under the optimal test conditions, differential pulse voltammetry was used to test pesticide molecules of different types with the same concentration. The test results are shown in the figure. Figure 4 Paraquat was also tested under the same conditions and the results were Figure 5 It can be concluded that FeCo-MOF material has good electrochemical response to paraquat, strong selectivity and strong environmental adaptability.
[0049] Test the detection performance of FeCo-MOF nickel foam electrode for paraquat.
[0050] The FeCo-MOF nickel foam working electrode, silver / silver chloride electrode and platinum counter electrode were placed in an electrolytic cell containing 200mL of 0.1M electrolyte solution with a pH of 7.4. Different volumes of paraquat solutions with concentrations of 20nM, 20μM and 20mM were added and stirred evenly. The test was performed using differential pulse voltammetry. A good oxidation peak was obtained in the paraquat concentration range of 1nM~5mM, as shown in Figure 6 (a). There is a good linear relationship between the oxidation peak current and the concentration, and the corresponding relationship is shown in Figure 6 (b). It can be concluded from the figure that the FeCo-MOF nickel foam electrode has a good detection performance for trace paraquat: the detection sensitivity is high (123.3μA μM -1 cm -1 ), which can realize rapid detection; the minimum detection concentration is 1nM, which fully meets the maximum residual amount of safety standards of many countries in the world; the detection range is between 1nM~5mM, which can meet the detection concentration requirements of different samples;
[0051] Test the anti-interference ability of FeCo-MOF nickel foam electrode in detecting paraquat.
[0052] After adding paraquat to the electrolytic cell of the three-electrode system, interfering pesticide molecules (dinotefuran, thiamethoxam, imidacloprid, phoxim and carbendazim) with a concentration 10 times that of paraquat were added to the electrolytic cell for detection. Interfering ions (K + ,Na + ,Fe 2+ ,Fe 3+ ,NH 4+ ,NO 3- ,Cl - ), the detected signal was consistent with the concentration of paraquat detected alone, with relative standard deviation RSD=0.32% (RSD<5%), indicating that the FeCo-MOF nickel foam electrode has strong anti-interference ability in detecting paraquat.
[0053] The long-term stability of FeCo-MOF nickel foam electrode in detecting paraquat was tested.
[0054] At the same paraquat concentration, the same electrode was tested three times every two days within one month, with a relative standard deviation (RSD) of 1.5%. After one month of testing, the response current of paraquat was 97.5% of the initial value, indicating that the FeCo-MOF nickel foam electrode has good long-term stability.
[0055] Example 1
[0056] Testing for paraquat in apples.
[0057] Step 1.1: Pretreatment of the working electrode
[0058] The nickel foam was cut into 1 cm × 2 cm size, and the cut nickel foam was placed in ethanol for ultrasonic treatment for 30 minutes to remove organic stains on the surface, and then washed with deionized water. Then, it was ultrasonically treated in dilute hydrochloric acid for 30 minutes to remove the oxide layer on the surface of the nickel foam skeleton, and then washed with deionized water and dried with cold air for use.
[0059] Wherein, the ethanol is analytically pure.
[0060] The dilute hydrochloric acid is analytical grade concentrated hydrochloric acid diluted with deionized water to a concentration of 3 M.
[0061] Step 1.2: Preparation of FeCo-MOF modified electrodes
[0062] Add N,N-dimethylformamide solution to a glass beaker, then add deionized water and anhydrous ethanol respectively, and stir evenly under a magnetic stirrer. Add terephthalic acid under stirring conditions, continue stirring for 30 minutes, and when the powder is completely dissolved, continue to add FeCl2·4H2O and CoCl2·6H2O to the solution. After stirring and dissolving evenly, add a small amount of hydrofluoric acid (HF) dropwise, stir for 30 minutes, and then transfer the solution to a polytetrafluoroethylene bottle. Put a piece of nickel foam prepared in step 1.1 in the polytetrafluoroethylene bottle, transfer it to the reactor, react at 120~150℃ for 12~18h, cool it down, wash it alternately with ethanol and deionized water 3 times, and dry it at 60℃ for 24h to obtain the FeCo-MOF in situ modified nickel foam working electrode.
[0063] Wherein, the N,N-dimethylformamide solution, terephthalic acid, FeCl2·4H2O and CoCl2·6H2O are all analytically pure chemicals.
[0064] Step 1.3: Testing for paraquat in real apple samples
[0065] Apple juice purchased from the market was filtered and added to 200mL of 0.1M phosphate electrolyte solution with pH = 7.4. The three electrodes of FeCo-MOF-modified nickel foam electrode working electrode, silver / silver chloride reference electrode and platinum sheet counter electrode were placed in the electrolytic cell and stirred evenly. The prepared paraquat solutions of different concentrations were added to the electrolyte, and the oxidation peak current intensity at different concentrations was recorded. The corresponding differential pulse voltammetry test curve is shown in Figure 7 (a). Each concentration was measured 3 times, and the recovery rate and relative standard deviation were calculated according to the linear equation of Figure 6 (b), as shown in Table 1:
[0066] Table 1 Recovery and relative standard deviation in apple samples
[0067]
[0068] Example 2
[0069] Detection of paraquat in human serum.
[0070] Step 2.1: Pretreatment of the working electrode
[0071] The specific processing steps are consistent with step 1.1 in Example 1.
[0072] Step 2.2: Preparation of FeCo-MOF modified electrodes
[0073] The specific processing steps are consistent with step 1.2 in Example 1.
[0074] Step 2.3: Detection of paraquat in real human serum samples
[0075] Human serum obtained from the hospital was diluted and added to 200mL of 0.1M phosphate electrolyte solution with pH = 7.4. The three electrodes of FeCo-MOF-modified nickel foam electrode working electrode, silver / silver chloride reference electrode and platinum counter electrode were placed in the electrolytic cell and stirred evenly. The prepared paraquat solution was added to the electrolyte, and the oxidation peak current intensity at different concentrations was recorded. The corresponding differential pulse voltammetry test curve is shown in Figure 7 (b). Each concentration was measured 3 times, and the recovery rate and relative standard deviation were calculated according to the linear equation of Figure 6 (b), as shown in Table 2:
[0076] Table 2 Recovery and relative standard deviation in human serum samples
[0077]
[0078] Embodiment 3:
[0079] Detection of paraquat in real tea samples.
[0080] Step 3.1: Pretreatment of the working electrode
[0081] The specific processing steps are consistent with step 1.1 in Example 1.
[0082] Step 3.2: Preparation of bimetallic FeCo-MOF modified electrodes
[0083] The specific processing steps are consistent with step 1.2 in Example 1.
[0084] Step 3.3: Detection of paraquat in real tea samples
[0085] Fresh tea juice purchased from the market was squeezed and filtered, and added to 200mL of 0.1M phosphate electrolyte solution with pH = 7.4. The three electrodes of FeCo-MOF-modified nickel foam electrode working electrode, silver / silver chloride reference electrode and platinum sheet counter electrode were placed in the electrolytic cell and stirred evenly. The prepared paraquat solution was added to the electrolyte, and the oxidation peak current intensity at different concentrations was recorded. The corresponding differential pulse voltammetry test curve is shown in Figure 7 (c). Each concentration was measured 3 times, and the recovery rate and relative standard deviation were calculated according to the linear equation of Figure 6 (b), as shown in Table 3:
[0086] Table 3 Recovery and relative standard deviation in tea samples
[0087]
[0088] The results in Tables 1-3 show that the FeCo-MOF modified electrode of the present invention is accurate in detecting real samples, with a recovery rate between 98.9% and 101.8% and a relative standard deviation RSD of <5%.
[0089] The above-described embodiments are only specific implementation methods of the present application, which are used to illustrate the technical solutions of the present application, rather than to limit them. The protection scope of the present application is not limited thereto. Although the present application is described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the aforementioned embodiments within the technical scope disclosed in the present application, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application. They should all be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A method for electrochemical detection of paraquat, characterized in that: include: Add deionized water and anhydrous ethanol to the N,N-dimethylformamide solution and mix them evenly; Add terephthalic acid and dissolve it; Add FeCl2·4H2O and CoCl2·6H2O and dissolve them; Add hydrofluoric acid and mix well; Add the pretreated nickel foam and carry out the reaction at a preset reaction temperature and for a preset reaction time; After the reaction is completed, the modified nickel foam is dried at a preset drying temperature for a preset drying time to obtain a FeCo-MOF in-situ modified nickel foam working electrode, so that the FeCo-MOF is anchored on the surface of the nickel foam, and the nickel foam working electrode has multiple active sites, and the nickel foam working electrode is used for electrochemical detection of paraquat; Differential pulse voltammetry was used to obtain the electrical signals of different concentrations of paraquat, so as to establish the relationship between the concentration of paraquat and the response current. The detection concentration range of paraquat is 1nM~5mM, and the sensitivity of paraquat detection is 123.3μA μM -1 cm -1 ; Among them, the pretreatment of nickel foam includes: The nickel foam was sonicated in ethanol; After rinsing with deionized water, treating in dilute hydrochloric acid of a preset concentration for a preset cleaning time; Rinse with deionized water and dry with cold air; The preset concentration of dilute hydrochloric acid is 3M, and the preset cleaning time is 30 minutes; The preset reaction temperature is 120-150°C, and the preset reaction time is 12-18h; the preset drying temperature is 60°C, and the preset drying time is 24h.
2. The electrochemical detection method of paraquat according to claim 1, characterized in that: The modified nickel foam is also washed alternately with ethanol and deionized water after being cooled before drying.
3. The electrochemical detection method of paraquat according to claim 2, characterized in that: include: The sample to be tested is added into a phosphate electrolyte solution having a preset phosphate concentration and a preset pH value.
4. The electrochemical detection method of paraquat according to claim 3, characterized in that: The preset phosphate concentration is 0.1 M, and the preset pH value is 7.4.
Citation Information
Patent Citations
Electrochemical sensor on basis of hierarchical porous Cu-BTC materials and application of electrochemical sensor to detecting glyphosate in pesticides
CN107271522A
Diamond-like bimetallic FeCo-MOF oxygen evolution electrocatalyst and preparation method thereof
CN111715298A
Preparation method and application of RuO2-loaded Ni-MOF electrode material
CN114892199A